Community Participation in Improving Environmental Order and Security through the Village Siskampling Program - Ahnaffarid Hanif Fadhil; Athhar Mahendra Sinatriya Adhyaksa; Suparmi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Order and environmental security are essential foundations for creating a harmonious and productive village community. A safe environment provides residents with a sense of comfort in carrying out their daily activities, whereas disorder can lead to anxiety, decreased productivity, and an increased potential for crime. This study aims to analyze how community participation contributes to improving environmental order and security through the Village Siskampling Program. The research employs a literature review method by analyzing 20 scientific articles published between 2020 and 2025, obtained from Google Scholar, SINTA, DOAJ, and Garuda. The selection process involved initial searching, title screening, abstract screening, publication year filtering, and full-text accessibility, resulting in 20 relevant articles. The findings indicate that the effectiveness of Siskampling is strongly influenced by community participation, discipline in night patrols, inter-resident communication, coordination among village institutions, and the support of security technologies such as CCTV and reporting applications. The identified challenges include low public awareness, limited security facilities, weak coordination, and dependence on paid security services. This study concludes that community participation is a key element in achieving village security and must be strengthened through continuous education, facilitation, and empowerment.